Recent Directions in Remote Engineering and Virtual Instrumentation - Sobh, Tarek M.; Pallis, Jani; Gupta, Navarun (International Journal of Online and Biomedical Engineering (iJOE), 2009)
The 6th Remote Engineering and Virtual instrumentation Conference (REV 2009) was held at the University of Bridgeport in Bridgeport, Connecticut, USA during the period of June 22 â?? 25, 2009. The conference brought together engineering researchers, educators, and professionals to explore the fundamentals, future, and application of remote engineering in both industry and academia. Participants delivered papers, presented demonstrations, research posters, and shared experiences in virtual engineering. REVâ??09 drew more than 100 engineers, scientists and educators from around the world. Most of the participants were from Europe, but many came from Asia, North and South America, the Middle East and as far as Australia. More than 60 papers were presented on topics ranging from Telerobotics to Virtual and Remote Labs. Workshops and Tutorials drew widespread interest and exhibitors displayed their products for integrating remote engineering into academia. Poster sessions discussed topics such as Robotic Surgery and Development of Remote Labs in Physics.The general objective of REV 2009 was to discuss fundamentals, applications and experiences within the field of online engineering, both in industry and academia. The conference presentations and papers addressed several emerging trends in online engineering, remote laboratories, virtual instrumentation and educational applications of remote engineering.